Diffusion-controlled premixed flames - Sirignano, William A. (Combustion theory and modelling, 2021)
Steady laminar flow structures with mixing, chemical reaction, and normal strain qualitatively representative of turbulent combustion at the small scales are analysed. A contrived counterflow configuration is examined to focus more easily on the premixed flames that are known to occur in multiple-flame structures; the premixed flame can be driven by a controlled heat source which is a surrogate for the diffusion flame in the practical multi-flame structure. Reduction to a one-dimensional similar form is obtained with density and properties variations. It is shown that premixed flames at fuel-rich or fuel-lean conditions sufficiently far from the stoichiometric condition are diffusion-controlled with a propagation velocity very weakly dependent on chemical kinetic details. In particular, heat diffused from a downstream source (i.e. the surrogate for a diffusion flame) is needed to sustain the flame. Effects of normal-strain rate, pressure level, and transport properties, combustible mixture composition, and heat source strength are determined through a parameter study with variations in Damköhler number, Prandtl number, upstream mass fractions of oxygen and propane fuel, and wall temperature. The premixed flame becomes less dependent on the downstream source as strain rate decreases and pressure increases. Small changes in heat and mass diffusivities have stronger effects than an order-of-magnitude change in Damköhler number.